Method of manufacturing ceramic porous laminate

JP2025022448APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023127031
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、簡便な方法で、基材となるセラミックス多孔質体に、均一な厚みのセラミックス多孔質層が形成されたセラミックス多孔質積層体を形成できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022448000002
    Figure 2025022448000002
  • Figure 2025022448000001
    Figure 2025022448000001
Patent Text Reader

Abstract

To provide a method for manufacturing a laminate by forming a layer of uniform thickness on a layer to be a base material by a simple process.SOLUTION: In a method for manufacturing a ceramic porous laminate, a ceramic porous layer is formed on the inner tube surface of a ceramic porous body having one or more tubes. The method comprises: a slurry solution supply step (1) for supplying a slurry solution having inorganic particles to the inside of the tube; and a coating film formation step (2) for forming a coating film layer of the slurry solution on the inner surface of the tube by passing a jig through the tube while supplying the slurry solution or after supplying the slurry solution.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a porous ceramic laminate. [Background technology]

[0002] Porous ceramic bodies are used in various fields as membranes having functions such as separation, concentration, or filtration of fluids, such as gases or liquids, such as microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, ion exchange membranes, and gas separation membranes.

[0003] It is important that porous ceramic bodies suitable for use in the fields described above can fully perform functions such as separation while allowing fluids to flow easily through the porous ceramic body. For this reason, they are usually composed of a laminate of two or more layers including a functional layer with a small pore diameter and a support layer with a large pore diameter that supports the functional layer.

[0004] For example, Patent Document 1 discloses a method for manufacturing a multi-layer filter in which a filtration membrane is attached to a porous support. Patent Document 1 discloses a method for manufacturing a multi-layer filter in which the porous support is immersed in a liquid to defoam the air in the pores of the porous support, the end of the porous support containing the liquid in the pores is airtightly sealed, and then a suspension containing a powder for forming a filtration membrane is brought into fluid contact with one side of the porous support, and the fluid contact of the suspension is continued for a predetermined time while maintaining the other side of the porous support at a lower pressure than the side that the suspension contacts, thereby attaching a filtration membrane made of the powder to one side of the porous support, and then performing a predetermined operation and then firing to manufacture a multi-layer filter.

[0005] Furthermore, Patent Document 2 discloses a method in which a ceramic sol liquid is poured into the cells of a porous substrate and passed through the cells, thereby adhering the ceramic sol onto the surfaces of the cells. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 63-66566 [Patent Document 2] JP 2009-189941 A Summary of the Invention [Problem to be solved by the invention]

[0007] When producing a laminate including two or more layers, it is desirable that the thickness of the layers formed is uniform. In the above-mentioned Patent Document 1, the device for producing the laminate is complicated, and in the method of Patent Document 2, the uniformity of the thickness of the layers formed is insufficient.

[0008] Therefore, an object of the present invention is to provide a method for producing a laminate by forming a layer of uniform thickness on a base layer in a simple manner. [Means for solving the problem]

[0009] The present invention which achieves the above object is as follows. [1] A method for producing a ceramic porous laminate by forming a ceramic porous layer on an inner surface of a ceramic porous body having one or more tubes, comprising the steps of: A slurry liquid supplying step (1) of supplying a slurry liquid containing inorganic particles to the inside of the pipe; and (2) a coating layer forming step of forming a coating layer of the slurry liquid on the inner surface of the pipe by passing a jig through the pipe while supplying the slurry liquid or after supplying the slurry liquid. [2] A manufacturing method described in [1], in which when the jig is projected in the direction of travel of the jig within the pipe, at least a portion of the outer periphery of the projection is curved. [3] The manufacturing method according to [1] or [2], wherein the slurry liquid is supplied to the inside of the pipe by injection, and the jig is passed through after the slurry liquid is injected. [4] The manufacturing method according to any one of [1] to [3], wherein the jig is moved within the pipe by flowing a fluid other than the slurry liquid from behind the jig in the direction of movement of the jig, and / or by sucking the slurry liquid from the direction of travel of the jig. [5] The method according to any one of [1] to [4], wherein the inner circumferential shape of the cross section perpendicular to the axial direction of the tube is a circle. [6] The method according to any one of [1] to [5], wherein the viscosity of the slurry is 2 Pa·s or more. [7] The method according to any one of [1] to [6], further comprising, after the coating layer forming step (2), a drying step (3) and / or a heat treatment step (4) of the coating layer. Effect of the Invention

[0010] According to the present invention, a ceramic porous laminate having a ceramic porous layer of uniform thickness formed on a ceramic porous body serving as a substrate can be formed by a simple method. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a photograph substituted for a drawing, showing a method for measuring the thickness of a ceramic porous layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The method for producing a ceramic porous laminate of the present invention is a method for producing a ceramic porous laminate by forming a ceramic porous layer on the inner surface of a ceramic porous body (hereinafter sometimes referred to as a substrate) having one or more tubes, and includes a slurry liquid supplying step (1) of supplying a slurry liquid containing inorganic particles to the inside of the tube, and a coating layer forming step (2) of passing a jig through the tube to form a coating layer of the slurry liquid on the inner surface of the tube while or after supplying the slurry liquid.

[0013] The outer peripheral shape of the substrate is not particularly limited, and the outer peripheral shape of the substrate in a cross section perpendicular to the axial direction may be a circle, an ellipse, a square, a rectangle, or the like. The substrate may have one or more tubes, that is, the substrate may be tubular or monolithic. In addition, the shape of the tube in a cross section perpendicular to the axial direction is preferably a circle.

[0014] The thickness (average value) of the substrate is preferably 400 to 8000 μm. When the substrate is monolithic, the thickness may be the average value of the closest distance between adjacent tubes on a plane perpendicular to the long axis. The length of the substrate in the axial direction is, for example, 50 to 5000 mm, preferably 500 to 3000 mm. When the substrate is tubular, the outer diameter of the substrate is, for example, 5 mm to 20 mm, and the inner diameter of the tube is, for example, 1 mm to 15 mm. When the substrate is monolithic, i.e., when it has two or more tubes, the outer diameter of the substrate is, for example, 5 mm to 100 mm, and the inner diameter of each tube is, for example, 0.1 mm to 10 mm.

[0015] The substrate preferably contains an inorganic oxide, and more preferably contains at least one metal oxide selected from the group consisting of Li2O, BeO, B2O3, Na2O, MgO, Al2O3, SiO2, K2O, CaO, ScO2, TiO2, V2O5, Cr2O3, ZnO, Ga2O3, GeO2, As2O5, Rb2O, SrO, Y2O3, ZrO2, Nb2O5, Ag2O, CdO, In2O3, SnO2, Sb2O5, TeO2, Cs2O, BaO, La2O3, Ta2O5, WO3, HgO, Tl2O, PbO, PbO2, and ThO2. More preferably, the substrate contains Al2O3 and one or more metal oxides other than Al2O3. The one or more metal oxides other than Al2O3 that are preferably contained in the base material can be arbitrarily selected from the metal oxides exemplified above, and the base material is particularly preferably glass containing Al2O3 and SiO2, and for example, an alumina base material manufactured by Nippon Tokushu Ceramics Co., Ltd. In this specification, the term "metal" is used to include semimetals such as Si.

[0016] The pore diameter of the substrate measured by mercury intrusion porosimetry is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 5 μm or more, and is preferably 20 μm or less, more preferably 18 μm or less, even more preferably 15 μm or less. The pore diameter means the pore diameter showing a peak in a graph with the pore diameter on the horizontal axis and the log differential pore volume on the vertical axis.

[0017] One or more intermediate layers may be formed on the inner surface of the substrate, and the present invention also includes forming a ceramic porous layer on the inner surface of the substrate via one or more intermediate layers.

[0018] The slurry liquid containing inorganic particles is a raw material for the ceramic porous layer formed on the substrate, and preferably contains a dispersant, a thickener and a solvent in addition to the inorganic particles.

[0019] The inorganic particles are preferably inorganic oxides, and in a preferred embodiment, the above-mentioned examples of metal oxides contained in the base material can be referred to, and it is particularly preferable that the inorganic particles are Al2O3. As Al2O3, commercially available α-alumina can be used, and there is no particular limitation, but examples thereof include AKP-3000, AKP-20, AA-10, and AA-5 manufactured by Sumitomo Chemical Co., Ltd. The volume-based cumulative 50% equivalent diameter of the inorganic particles is, for example, about 0.1 to 20 μm. The concentration of the inorganic particles in the slurry is, for example, 1 to 35 mass%.

[0020] The coating amount of inorganic particles is 0.1 g / cm 2 or less, and may be 0.005 g / cm 2 It is preferable that the content is 0.006 g / cm or more. 2 More preferably, it is 0.0071 g / cm or more. 2 More preferably, it is equal to or greater than this.

[0021] The dispersant can suppress the aggregation of inorganic particles in the slurry. The dispersant may be any of cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. Among them, anionic surfactants such as polycarboxylate ammonium salts and polycarboxylate amine salts are preferred, and SN Dispersant 5020, SN Dispersant 5023, SN Dispersant 5027, SN Dispersant 5468, Noparfa D-6010, Nopcol 5200, Nopcosant RFA, Nopcosperse 6100, and Nopcosperse 6150 manufactured by San Nopco Co., Ltd. may be used. The concentration of the dispersant in the slurry (in terms of active ingredient) is, for example, 0.01% by mass or more and 10% by mass or less, and preferably 0.1% by mass or more and 8% by mass or less, based on 100% by mass of inorganic particles in the slurry.

[0022] Examples of the thickener include methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyalkylene oxide, polyvinyl alcohol, sodium polyacrylate, polyvinylpyrrolidone, polyacrylamide, polydimethylaminoethyl methacrylate, etc., and hydroxypropyl methyl cellulose is particularly preferred. The amount of the thickener to be added can be appropriately adjusted depending on the target slurry viscosity.

[0023] The solvent may be water or an organic solvent.

[0024] After the inorganic particles are mixed with the preferably used dispersant, thickener and solvent, it is also preferable to carry out a defoaming treatment.

[0025] It is also preferable to adjust the viscosity of the slurry liquid, and the viscosity of the slurry liquid is, for example, 2 Pa·s or more. The viscosity of the slurry liquid is preferably 4 Pa·s or more, more preferably 10 Pa·s or more, and is preferably 45 Pa·s or less, more preferably 40 Pa·s or less, and even more preferably 38 Pa·s or less. By setting the viscosity within such a range, the thickness of the laminated ceramic porous layer can be made uniform, and clogging of the tubes in the substrate can be avoided.

[0026] When supplying the slurry liquid to the substrate and when passing the jig through the pipe, it is preferable to arrange the substrate so that the axial direction thereof is vertical.

[0027] In the slurry liquid supplying step (1), the slurry liquid may be supplied from either end of the substrate, but when the substrate is arranged so that its axial direction is vertical, it is preferable to supply the slurry liquid from the lower end of the substrate. The supply of the slurry liquid may be carried out by injecting the slurry liquid from the end of the substrate, or by masking the substrate end face other than the hole of the tube and the substrate side surface and immersing the substrate in the slurry liquid, but it is preferable to supply the slurry liquid by injection from the end of the substrate (particularly one end).

[0028] In the coating layer forming step (2) of the slurry liquid, by using a jig, the excess of the slurry liquid supplied to the inner tube surface of the substrate can be discharged, and the slurry liquid can be uniformly applied to the inner tube surface of the substrate. The jig may be passed through the tube after the slurry liquid is supplied, or may be passed through the tube while the slurry liquid is being supplied. It is preferable to supply the slurry liquid to the inside of the tube and pass the jig after the slurry liquid is supplied, and it is more preferable to supply the slurry liquid to the inside of the tube by injection and pass the jig after the slurry liquid is injected.

[0029] The direction of supply of the slurry liquid and the direction of passing the jig may be the same or different. When the substrate is arranged so that the axial direction is vertical, it is preferable to pass the jig from the upper end after the slurry liquid is supplied from the end of the substrate to the inner tube surface of the substrate.

[0030] The method of passing the jig through the tube of the substrate includes (i) flowing a fluid other than the slurry liquid from the rear of the jig in the direction of the jig's movement, (ii) sucking the slurry liquid from the direction of the jig's advancement, or (iii) performing both of these. In addition, when the substrate is arranged so that the axial direction is vertical, (iv) the jig may be passed through by dropping it from the upper end of the substrate under its own weight. The fluid includes a gas such as air. The method of moving the jig is particularly preferably (i) to (iii), and more preferably (i). In the embodiment (i), when a fluid other than the slurry liquid is flowed, the pressure of the fluid may be, for example, 0.01 MPa to 0.5 MPa.

[0031] After the jig is passed through the tube of the substrate, the tube may be pressurized by flowing air or other fluid into the tube for a certain period of time, or may not be held in that state. By holding the tube in a pressurized state for a certain period of time, the solvent, thickener, etc. in the slurry can be discharged to the outside of the tube through the pores of the substrate. The pressurizing pressure is, for example, 0.01 MPa to 0.5 MPa, and the holding time is, for example, 0.01 to 30 minutes.

[0032] The material of the jig is not particularly limited, and a jig made of resin, metal, ceramic, or the like can be used. The shape of the jig is preferably such that when projected in the moving direction of the jig inside the pipe, at least a part of the outer periphery of the projection is curved, specifically, a coil shape, a cylindrical shape, an elliptical cylindrical shape, a cone shape, a spherical shape, and a shape combining these shapes can be mentioned. In addition, among these shapes, a shape other than a coil shape is preferably cut with one or more planes parallel to the moving direction of the jig, and a part of the outer periphery is removed while leaving a part of it, and the jig may be moved inside the pipe while rotating. The shape of the jig is preferably such that the inner periphery shape of the cross section perpendicular to the axial direction of the pipe is a circle, specifically, a cylinder or a sphere, and a sphere is more preferable. The size of the jig may be appropriately adjusted according to the thickness of the ceramic porous layer to be formed within a range that can be inserted inside the pipe.

[0033] After forming a coating layer of the slurry liquid on the inner surface of the pipe using the jig, it is preferable to carry out at least one of a drying step (3) for drying the coating and a heat treatment step (4).

[0034] Drying is preferably carried out at a temperature of 100° C. or less, and the coating layer is preferably air-dried, and the temperature of the air blown onto the coating may be room temperature or may be hot air in the range of 100° C. or less. The speed of the air blown onto the coating surface is, for example, 0.05 to 1 m / sec.

[0035] In addition, the heat treatment step (4) can promote sintering of inorganic particles contained in the slurry liquid, improve the strength of the layer formed from the slurry liquid, and appropriately adjust the porosity. The heat treatment step (4) may be performed after the coating layer forming step (2) without going through the drying step (3), but is preferably performed after the drying step (3), and is preferably performed at a temperature of more than 100°C to 1500°C, for example, preferably 300 to 1500°C, more preferably 500 to 1500°C, and even more preferably 1000 to 1500°C. The heat treatment time is, for example, 30 minutes to 10 hours, preferably 1 to 5 hours.

[0036] The thickness of the ceramic porous layer formed on the tube inner surface of the substrate may be adjusted by, for example, adjusting the viscosity of the slurry liquid; performing a series of steps including the slurry liquid supply step (1) and the slurry liquid coating layer forming step (2) (and, if necessary, the drying step (3) and / or the heat treatment step (4)) two or more times; adjusting the concentration of inorganic particles in the slurry; or adjusting the size of the jig. When the series of steps including the steps (1) and (2) for forming the ceramic porous layer are performed two or more times as described above, it is preferable that the movement direction of the jig relative to the substrate in at least any of the second and subsequent steps is opposite to the movement direction of the jig relative to the substrate in the first step.

[0037] In the present invention, when a ceramic porous laminate in which a ceramic porous layer is formed on the tube inner surface of a substrate via one or more intermediate layers is produced, the intermediate layer is preferably a ceramic porous layer containing inorganic particles, and it is more preferable to form the intermediate layer by the production method of the present invention. That is, it is preferable to perform a slurry liquid X supplying step (1X) of supplying a slurry liquid X containing inorganic particles X to the inside of a tube of a ceramic porous body having one or more tubes, and a coating layer forming step (2X) of the slurry liquid X to form an intermediate layer on the tube inner surface, and further perform a slurry liquid Y supplying step (1Y) of supplying a slurry liquid Y containing inorganic particles Y to the inside of the tube on which the intermediate layer is formed, and a coating layer forming step (2Y) of the slurry liquid Y. After the coating layer forming step (2X), a drying step (3X) and / or a heat treatment step (4X) may be further performed, or a heat treatment step (4X) may be further performed after the drying step (3X). In addition, the drying step (3Y) and / or the heat treatment step (4Y) may be performed after the coating layer forming step (2Y), or the heat treatment step (4Y) may be performed after the drying step (3Y). The steps (1X) and (1Y) are the same as the above-mentioned step (1) except that the name of the slurry liquid is specified, and the description of step (1) can be entirely referred to. The steps (2X) and (2Y) are the same as the above-mentioned step (2) except that the name of the slurry liquid is specified, and the description of step (2) can be entirely referred to. The steps (3X) and (3Y), and the steps (4X) and (4Y) can also be entirely referred to the descriptions of steps (3) and (4), respectively.

[0038] The inorganic particles X contained in the slurry liquid X and the inorganic particles Y contained in the slurry liquid Y are preferably the inorganic oxides exemplified above as preferred embodiments of the substrate, and are preferably both Al2O3. In addition, it is preferable that the inorganic particles X contain inorganic particles X1, and the inorganic particles Y contain inorganic particles Y1 having a smaller average particle size than the inorganic particles X1. In this case, the inorganic particles X may contain inorganic particles X2 having a smaller average particle size than the inorganic particles X1 together with the inorganic particles X1, and the inorganic particles X2 and the inorganic particles Y1 may be the same or different. It is preferable that the inorganic particles X1, X2, and Y1 are all Al2O3. In this way, even if the pore diameter of the substrate is relatively large, the ceramic porous layer can be formed uniformly on the substrate. The volume-based cumulative 50% equivalent diameter of inorganic particles X1 is preferably 1 to 20 μm, the volume-based cumulative 50% equivalent diameter of inorganic particles Y1 is preferably 0.05 μm or more and less than 1 μm, and the volume-based cumulative 50% equivalent diameter of inorganic particles X2 is preferably 0.05 μm or more and less than 1 μm.

[0039] Furthermore, even when the intermediate layer is formed by the manufacturing method of the present invention, it is preferable to adjust the thickness of the ceramic porous layer by performing a series of steps including the slurry liquid Y supply step (1Y) and the slurry liquid Y coating layer forming step (2Y) (and, if necessary, the drying step (3Y) and the heat treatment step (4Y)) two or more times, and it is more preferable to reverse the movement direction of the jig relative to the substrate in at least one of the second and subsequent steps in the ceramic porous layer forming step to the movement direction of the jig relative to the substrate in the first step in the ceramic porous layer forming step. In addition, it is also possible to form two or more intermediate layers or increase the thickness of the intermediate layer by performing a series of steps including (1X) and (2X) (and, if necessary, (3X) and / or (4X)) two or more times.

[0040] The ceramic porous laminate obtained by the present invention has a ceramic porous layer formed on the inner surface of a ceramic porous body having one or more tubes, with or without an intermediate layer. The intermediate layer has an average thickness of, for example, 3 to 60 μm. The ceramic porous layer formed by the present invention has an average thickness of, for example, 5 to 100 μm, more preferably 20 to 80 μm. According to the present invention, the variation in thickness of the ceramic porous layer formed on the inner surface of the tube of the substrate can be suppressed, and in particular, the variation in thickness at both ends in the axial direction of the tube can be suppressed. The difference in thickness of the ceramic porous layer formed on the inner surface of the tube of the substrate at both ends in the axial direction of the tube (the difference in the average value at each end) can be, for example, 16 μm or less, preferably 13 μm or less, more preferably 10 μm or less, and the lower limit is most preferably 0 μm, but may be about 1 μm.

[0041] The ceramic porous laminate obtained by the present invention can be used as a microfiltration membrane, an ultrafiltration membrane, or a nanofiltration membrane, and if necessary, by laminating a functional layer thereon, the laminate can be used as a microfiltration membrane, an ultrafiltration membrane, a nanofiltration membrane, a reverse osmosis membrane, an ion exchange membrane, a separation membrane for gases, etc.

[0042] Examples of the functional layer include zeolite, MOF (Metal Organic Frameworks), porous silica membrane, and porous alumina membrane. A separation membrane with a functional layer can be produced by applying a liquid containing inorganic particles or MOF that constitute the functional layer to the surface of the ceramic porous laminate obtained by the present invention and reacting it. The synthesis conditions can be appropriately selected depending on the functional layer to be laminated, and may be, for example, 80 to 800°C for 1 to 72 hours. EXAMPLES

[0043] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are included in the technical scope of the present invention.

[0044] [Method of measuring pore diameter] The pore diameter D50 of the substrate was measured by mercury intrusion porosimetry using an Autopore V9620 (Micromeritics) after drying the substrate at 120°C for 4 hours. The mercury intrusion porosimetry produced a graph with the pore diameter on the horizontal axis and the cumulative log differential pore volume on the vertical axis, and the cumulative 50% equivalent diameter was obtained. The details of the measurement conditions are as follows. Adv. Contact Angle: 140.0° Rec. Contact Angle: 140.0° Mercury Temperature:21°C Sample Mass: 1.0g Assembly Mass: 1.0g Penetrometer Volume: 1.0mL Penetrometer Mass: 1.0g Report Range:1.07 to 59,256.30psia

[0045] [Method for measuring particle size of metal oxides] The particle size distribution of the alumina used in the examples and comparative examples was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EX II, 0.2 mass% aqueous solution of sodium hexametaphosphate, manufactured by Microtrac Corporation), and the volume-based cumulative 50% equivalent diameter was measured.

[0046] [Method of measuring viscosity of slurry liquid] The viscosity of the slurry used in the examples and comparative examples was measured after the temperature of the slurry was brought to room temperature using a B-type viscometer (BL model, manufactured by Toki Sangyo Co., Ltd.) at room temperature and at a stirring speed according to the manual for the device.

[0047] [Method for measuring ceramic porous layer thickness] The cylindrical porous ceramic laminates obtained in the following Examples and Comparative Examples were cut out perpendicularly to the axial direction, with 3-4 cm portions from both ends. The laminates were embedded in resin and mechanically polished so that the cut surfaces could be observed. The polished surfaces were platinum-deposited and observed and photographed at 500x magnification using a FE-SEM (JEOL, JSM-7500FA). A certain angle (0 degrees) of the cylinder was arbitrarily determined, and angles from 0 degrees to 90 degrees, 180 degrees, and 270 degrees were set. From the obtained images, the thickness of the layer (porous ceramic layer) containing the following alumina powder X, which has a cumulative 50% equivalent diameter on a volume basis of about 0.5 μm and is formed on the layer (intermediate layer) containing AA-10 particles, was measured at the four positions mentioned above. At each of the positions of 0 degrees, 90 degrees, 180 degrees, and 270 degrees mentioned above, the distance from the outermost layer of the laminate to the layer adjacent to the outermost layer was measured at any four points. More specifically, as shown in Figure 1, four AA-10 particles located on the outermost side of the layer adjacent to the outermost layer were arbitrarily selected, and the distance from the surface of the AA-10 particles to the outermost layer was measured. The average value of these distances was taken as the thickness at each of the positions of 0 degrees, 90 degrees, 180 degrees, and 270 degrees.

[0048] Example 1 (base material) As the substrate, an alumina substrate A-13 (cylindrical shape with pore diameter of 11 μm, inner diameter of 7.0 mm, outer diameter of 9.5 mm, and length of 30 cm) containing alumina and SiO 2 manufactured by Nippon Tokushu Ceramics Co., Ltd. was used.

[0049] (Formation of the intermediate layer) In this embodiment, the intermediate layer was also formed by the manufacturing method of the present invention. First, alumina powder AA-10 manufactured by Sumitomo Chemical Co., Ltd. (cumulative 50% equivalent diameter on a volume basis is approximately 14 μm), hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant were mixed in water at concentrations of 13.0 mass%, 1.9 mass%, and 1.3 mass%, respectively, and the mixture was degassed to prepare a slurry for the intermediate layer (hereinafter, slurry S1).

[0050] Next, the slurry S1 was filled into a catheter syringe manufactured by Terumo Corporation, and the syringe was left standing for 1 hour with the outlet facing downward. A tube was attached to the tip of the catheter syringe manufactured by Terumo Corporation, and one end of the substrate placed vertically was placed downward, the tip of the tube was connected to the end (hereinafter referred to as end A; the other end opposite end A is referred to as end B), and the slurry S1 was injected into the entire inner circumference of the substrate. After injecting the slurry S1, a resin ball with a diameter of 6.35 mm was set at the end B (upper end side) of the substrate, and the slurry S1 was discharged by flowing air from the end B at an air pressure of 0.1 MPa to move the ball from the end B to the end A, and after discharging the slurry S1, the ball was held at the end A and maintained at 0.1 MPa for 600 seconds. After 600 seconds, the substrate was rotated at 6.9 rpm while blowing hot air of about 0.1 m / s over the inner circumferential surface of the substrate to dry it, and an intermediate layer containing AA-10 particles was formed on the inner circumferential surface of the substrate.

[0051] (Preparation of slurry for ceramic porous layer) Commercially available alumina powder X (cumulative 50% equivalent diameter on a volume basis is approximately 0.5 μm), hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 (active ingredient 41%) as a dispersant were mixed in water at concentrations of 9.0 mass %, 1.0 mass %, and 0.9 mass %, respectively, and the mixture was degassed to prepare a slurry for a ceramic porous layer (hereinafter, slurry S2).

[0052] (Formation of ceramic porous layer 1) The slurry S2 was filled into a catheter syringe manufactured by Terumo Corp., and the syringe was left standing with the outlet facing downward for 1 hour. A tube was attached to the tip of the catheter syringe manufactured by Terumo Corp., and the tip of the tube was connected to the end A of the substrate having a layer (intermediate layer) containing AA-10 particles formed on the inner circumferential surface thereof, which was placed vertically, with the end A facing downward, and the slurry was injected into the entire inner circle of the substrate. After the slurry was injected, a resin ball with a diameter of 6.0 mm was set at end B (upper end side) of the substrate, and air was flowed from end B at an air pressure of 0.02 MPa to move the ball from end B to end A, thereby discharging the slurry. While rotating the substrate at 6.9 rpm, hot air of about 0.1 m / s was blown across the inner circumferential surface of the substrate to dry it, and the ceramic porous layer containing the alumina powder X was formed on the layer containing AA-10 particles (intermediate layer). The substrate having the layer containing AA10 particles (intermediate layer) and the ceramic porous layer containing alumina powder X formed on the inner circumferential surface was heat-treated at 1200°C for 3 hours.

[0053] (Formation of ceramic porous layer 2) After the heat treatment, the slurry S2 was poured into the substrate with end B facing down, a ball was set at end A (upper end) of the substrate, and air was allowed to flow from end A. The same procedure as in “Formation of ceramic porous layer 1” was repeated to obtain a porous ceramic laminate.

[0054] Example 2 The porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that the composition of the slurry S2 was changed to a slurry containing alumina powder X, hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant at concentrations of 9.0 mass%, 1.3 mass%, and 0.9 mass%, respectively.

[0055] Example 3 The porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that the composition of the slurry S2 was changed to a slurry containing alumina powder X, hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant at concentrations of 9.0 mass%, 1.5 mass%, and 0.9 mass%, respectively.

[0056] Example 4 The porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that the composition of the slurry S2 was changed to a slurry containing alumina powder X, hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant at concentrations of 9.0 mass%, 1.8 mass%, and 0.9 mass%, respectively.

[0057] Example 5 The porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that the composition of the slurry S2 was changed to a slurry containing alumina powder X, hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant at concentrations of 9.0 mass%, 2.0 mass%, and 0.9 mass%, respectively.

[0058] Comparative Example 1 In the same manner as in Example 1, an intermediate layer was formed on the inner surface of an alumina substrate A-13 manufactured by Nippon Tokushu Ceramics Co., Ltd., and then, in the same manner as in Example 1, a slurry S2 was injected into the inside of the substrate on whose inner surface the intermediate layer was formed. After injecting the slurry S2, the tip of a 50 ml catheter syringe manufactured by Terumo Corporation was inserted into end A of the substrate (substrate with an intermediate layer formed on the inner circumferential surface) that was placed vertically with end A facing downward, and the slurry was manually aspirated and discharged with the syringe. As a result, the slurry clogged the inside of the tube hole in the substrate, and a laminate could not be obtained.

[0059] Comparative Example 2 The porous ceramic laminate of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the composition of the slurry S2 was changed to a slurry containing alumina powder X, hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant at concentrations of 9.0 mass%, 1.3 mass%, and 0.9 mass%, respectively.

[0060] The results are shown in Table 1.

[0061]

Table 1

Claims

1. A method for producing a ceramic porous laminate by forming a ceramic porous layer on an inner surface of one or more tubes of a ceramic porous body, the method comprising the steps of: A slurry liquid supplying step (1) of supplying a slurry liquid containing inorganic particles to the inside of the pipe; and (2) a coating layer forming step of forming a coating layer of the slurry liquid on the inner surface of the pipe by passing a jig through the pipe while supplying the slurry liquid or after supplying the slurry liquid.

2. 2. The manufacturing method according to claim 1, wherein when the jig is projected in the direction of travel of the jig within the pipe, at least a part of the outer periphery of the projection is curved.

3. The manufacturing method according to claim 2 , wherein the slurry liquid is supplied to the inside of the pipe by injection, and the jig is passed through after the slurry liquid is injected.

4. The manufacturing method described in claim 3, wherein the jig is moved within the pipe by flowing a fluid other than the slurry liquid from behind the jig in the direction of movement of the jig, and / or by sucking the slurry liquid from the direction of travel of the jig.

5. The method according to claim 3 , wherein the inner circumferential shape of the cross section perpendicular to the axial direction of the pipe is a circle.

6. The method according to claim 3, wherein the viscosity of the slurry is 2 Pa·s or more.

7. The method according to claim 1, further comprising a step of drying the coating layer (3) and / or a step of heat treating the coating layer (4) after the coating layer forming step (2).

Citation Information

Patent Citations

  • One component toner

    JP1988066566A

  • Method of manufacturing ceramic filter

    JP2009189941A